1996
DOI: 10.1111/j.1467-8624.1996.tb01896.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Influences on False Belief Access: Specific Sibling Influences or General Apprenticeship?

Abstract: Some recent studies have found a relation between the number of siblings 3-4-year-old children have and their performance on false belief tasks. 2 experiments reported here examine a variety of factors in children's social environments, including daily contact with peers and adults as well as the numbers of their siblings, on a battery of false belief tests. In Experiment 1, 82 preschoolers were studied in Rethymnon, Crete, in order to obtain a range of extended kin available as a resource for the child. In Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 22 publications
(33 reference statements)
11
120
0
2
Order By: Relevance
“…It remains to be seen how the present findings, showing stronger effects of non-familial over familial experiences on the development of referential communicative adjustments, can be reconciled with previous reports, showing that measures of familial interactions predicted ‘false belief understanding’ [12], [13], as assessed with verbal reports. One possibility is that the communicative adjustments observed in this study might be mainly driven by children’s assumptions on the presumed cognitive capacities of the addressees, rather than by children’s understanding that the beliefs, desires, or intentions of other agents differ from reality [11], [13].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It remains to be seen how the present findings, showing stronger effects of non-familial over familial experiences on the development of referential communicative adjustments, can be reconciled with previous reports, showing that measures of familial interactions predicted ‘false belief understanding’ [12], [13], as assessed with verbal reports. One possibility is that the communicative adjustments observed in this study might be mainly driven by children’s assumptions on the presumed cognitive capacities of the addressees, rather than by children’s understanding that the beliefs, desires, or intentions of other agents differ from reality [11], [13].…”
Section: Discussionsupporting
confidence: 67%
“…Given that the extent and nature of the social interactions experienced by children is widely thought to influence the development of their social understanding [5], [7], [12], [13], we considered two main sources of social interactions experienced by children, namely familial and non-familial experiences, reconstructed from interviews with the parents of the children. Familial experiences were indexed with the parents’ level of education (11 levels, 7.4±1.6, group mean ± SD, range 4.5–10.5) and years of experience with siblings (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sibling sex may also be a factor as Ruffman et al [62] found opposite sex pairs to have better ToM skills than same sex pairs. Other studies, however, found no relationship between age or number of siblings and ToM skills [64] [65]: Lewis et al [66] found that ToM skills increased with the number of other adults and non-siblings interacting with a child, i.e. the total network of interactions has to be taken into account.…”
Section: Introductionmentioning
confidence: 97%
“…Typically, the explanation of the delayed or deviant development is that sensory impairment, whether auditory or visual, prevents the child from perceiving all information necessary to fully partake in the social interaction, hence missing out on much of the experiences on which development relies (Garfield et al, 2001). There are strong indications that individuals need ample opportunities to interact and socialize with others in order to develop ToM to full and nuanced extent (Lewis et al, 1996;Garfield et al, 2001). As stated previously, there are correlations between language proficiency and ToM (Schick et al, 2007;Garfield et al, 2001;Slade, 2005).…”
Section: Theory Of Mind (Tom)mentioning
confidence: 78%